Maternal gestational diabetes and infant feeding, nutrition and growth: a systematic review and meta-analysis. Issue 11 (22nd January 2020) - Manerkar, Komal; Harding, Jane; Conlon, Cathryn; McKinlay, Christopher
Abstract : Abstract: Gestational diabetes mellitus (GDM) is a major health problem, with increased risks of obesity and diabetes in offspring. However, little is known about the effect of GDM on infant feeding, nutrition and growth, and whether these factors play a role in mediating these risks. We systematically reviewed evidence for the effect of GDM on infant feeding, nutrition and growth. We searched MEDLINE, Web-of-Science, Embase, CINAHL and CENTRAL for studies that reported outcomes in infants <2 years who were and were not exposed to GDM. Studies of pre-gestational diabetes were excluded. Meta-analysis was performed for three epochs (1–6, 7–12, 13–24 months), using inverse-variance, fixed-effects methods. Primary outcomes were energy intake (kJ) and BMI (kg/m 2 ). Twenty-five studies and 308 455 infants were included. Infants exposed to GDM, compared with those not exposed, had similar BMI at age 1–6 months (standardised mean difference (SMD) = 0·01, 95 % CI −0·04, 0·06; P = 0·69) and 7–12 months (SMD = 0·04, 95 % CI −0·01, 0·10; P = 0·09), reduced length at 1–6 and 7–12 months, increased whole-body fat at 1–6 months, higher rates of formula supplementation in hospital, shorter duration of breast-feeding and decreased rates of continued breast-feeding at 12 months. Breast milk of women with GDM had lower protein content. There was no association between GDM and infant weight and skinfold thickness. No data were available for nutritional intake and outcomes at 13–24 months. Low- or very low-quality evidence suggests GDM is not associated with altered BMI in infancy, but is associated with increased fat mass, high rates of formula use and decreased duration of breast-feeding.